Detection of heavy metal and antibiotics resistant in some isolates of Bacillus isolated from Iraqi soil - Al- Khafaji, K. A.; Saffa A. R.; abid al- Hadi (Journal of Madenat Alelem University College, 2016)
Heavy metals and antibiotic resistance were screened for local isolates of Bacillus species which either alkalophil or thermophil. Differences in their heavy metals resistant were detected against Pb, Hg, Cr, Co, Mo and Zn. Antibiotic resistant for ampicillin, cholaramphenicol, tetracycline, kanamycin, rifampcin and streptomycin were detected. Some of the isolates belong to B. alcalophilus have heavy metals and antibiotic resistance. DNA electrophoresis showed difference in plasmids size and electrophoresis profile of some isolates of B. alcalophilus, no plasmid was recognized in DNA samples of B. stearothermophilus.